PENERAPAN MODEL PAIKEM MELALUI PENDEKATAN INDEX CARD MATCH UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA - Ijah Khodijah; Jamali Sahrodi; Hendri Handoko (Program Studi Pendidikan Matematika, FKIP Universitas Muhammadiyah Cirebon, 2018)
The low level of mathematical problem solving abilities of students is motivated by a less active learning model and still teacher-centered which result in students being less active in learning so that mathematical problem solving skills are still lacking. On of the learning models that can influence problem solving skills is the PAIKEM model through the index card match approach. So, the problem in this study is how much influence the PAIKEM model has through the index card match approach. This study aims to: 1) Knowing the application of the PAIKEM model through the index card match approach in mathematics learning has a better effect than conventional learning, in terms of students mathematical problem solving, 2) Knowing students responses to mathematics learning with the PAIKEM model trough an index card match approach. This type of research uses experimental quantitative research with the design of the pretest-posttest control group. The population in this study were all eighth grade students of SMP Negeri 3 Palimanan Cirebon academic year 2018/2019. The sample in this study was class VIII F as the experimental class and class VIII E as control class. The instrument used was a problem solving ability test and questionnaire. The result showed: 1) The PAIKEM model through the index card match give a better effect than conventional learning. This is evidenced by the result of the independent test, that is the significance value 0,000 < 0,05. That is, there are differences in the average test scores of mathematical problem solving abilities, that is 80,06 for the experimental class and 71,35 for the control class. 2) Students responses to mathematics learning with the PAIKEM model through the index card match approach has an average of 80,7% in the good categories. Keywords: PAIKEM Model, Index Card Match, Problem Solving Ability